Inclusion/exclusion criteria in late life depression antidepressant efficacy trials. (22nd August 2016) - Zimmerman, Mark; Multach, Matthew D.; Clark, Heather L.; Walsh, Emily; Rosenstein, Lia K.; Gazarian, Douglas
Abstract : Objective: The generalizability of antidepressant efficacy trials (AETs) has been questioned. No studies have examined the inclusion/exclusion criteria used in placebo‐controlled studies of late life depression and compared them to the criteria used in non‐late life AETs. Method: We conducted a comprehensive literature review of placebo‐controlled AETs published from January, 1995 through December, 2014. We compared the inclusion/exclusion criteria used in the 18 studies of late life depression to those used in non‐late life depression. Results: There were nine inclusion/exclusion criteria that were used in more than half of the late life depression AETs: minimum severity on a symptom severity scale (100.0%), significant suicidal ideation (77.8%), psychotic features during the current episode of depression or history of a psychotic disorder (94.4%), history of bipolar disorder (77.8%), diagnosis of alcohol or drug abuse or dependence (83.3%), presence of a comorbid nondepressive, nonsubstance use Axis I disorder (55.6%), episode duration too short (66.7%), and an insufficient score on a cognitive screen (88.3%) or the presence of a cognitive disorder (55.6%). There were some differences between the late life and non‐late life depression studies—use of a screening measure of cognitive functioning, presence of a cognitive disorder such as dementia, and the minimum depression severity cutoff score required at baseline. Conclusions: The inclusion/exclusion criteria in AETs of late life depression were generally similar to the criteria used in non‐late life depression AETs. Copyright © 2016 John Wiley & Sons, Ltd.